2022
DOI: 10.1007/s41105-021-00371-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep patterns of college students in Israel during COVID-19 lockdown, a sleep diaries study

Abstract: To prevent and reduce the spread of COVID-19, governments around the world apply social restrictions and lockdowns. Such lockdowns significantly alter daily routine and habits. A growing body of research indicates that lockdowns affect sleep and circadian rhythms. The current study further explores this effect using sleep logs for a relatively long duration including lockdown and post-lockdown periods in Israel. For two consecutive months, both during lockdown and during post-lockdown periods, from March 13th,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Nevertheless, the circadian preference of individuals is conserved across conditions. [1]." We agree that the effect of COVID-19 lockdown on sleep is interesting.…”
Section: Dear Editormentioning
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, the circadian preference of individuals is conserved across conditions. [1]." We agree that the effect of COVID-19 lockdown on sleep is interesting.…”
Section: Dear Editormentioning
confidence: 79%
“…We read the article entitled “Changes in sleep patterns of college students in Israel during COVID-19 lockdown, a sleep diaries study” [ 1 ]. Lan et al mentioned that “ A lockdown period affects sleep–wake behavior: during lockdown people sleep duration is increased and their sleep onset is delayed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 78 In Israel, a significant reduction in sleep duration from lockdown to postlockdown period for workdays and weekends was reported. 79 …”
Section: Resultsmentioning
confidence: 99%
“…78 In Israel, a significant reduction in sleep duration from lockdown to postlockdown period for workdays and weekends was reported. 79 Sleep quality Furthermore, 85.55% of students reported poor SQ and 67.9% were females. It was found that sleep disturbance and daytime dysfunction were poorer in students with higher body mass index ranges.…”
Section: Sleep Durationmentioning
confidence: 99%